Analisis Penerapan Disiplin Pegawai Negeri Sipil di Lingkungan Pemerintah Kabupaten Kotawaringin Barat - Adyani, Sofia; Indrajaya, Kusnida; Listyarini, Sri (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2022)
One indication of the low quality of civil servants is the existence of disciplinary violations within the West Kotawaringin Regency Government. Constraints faced by a Civil Servant in the application of Civil Servant discipline are the lack of strict sanctions given by the authorized official and the erosion of Civil Servant discipline. The purpose of this study is to analyze the application of civil servant discipline based on Government Regulation No. 53 of 2010 concerning Civil Servant Discipline and analyze the factors that encourage and hinder the discipline of Civil Servants in the West Kotawaringin Regency Government with reference to the theory proposed by Nitisemito, namely Purpose and Ability, Leading Example, Prosperity, Threat and Assertiveness. This research method is qualitative. Data was collected through interviews, observation and documentation, the selection of informants was carried out by purposive sampling, namely the selection of informants with the consideration that the informants really knew or were directly involved with the research focus. The data analysis technique used is data reduction, data presentation and conclusion drawing. The solution to the disciplinary problem is the existence of sanctions or strict action if a Civil Servant is proven to have committed a disciplinary violation which aims to provide a deterrent effect and shock therapy so that other Civil Servants do not imitate or commit more serious violations.